EVALUATION OF NEPHROPROTECTIVE POTENTIALS OF AQUEOUS EXTRACT OF Trigonella foenum-greacum Linn. AGAINST GENTAMICIN INDUCED RENAL DAMAGE IN ALBINO RATS - SIVASUBRAMANIAN RENGARAJU; KADHIRAVAN MURUGAIAH; BRINDHA PEMMAIAH (International Journal of Pharma and Bio Sciences, 2016)
Nephrotoxicity is considered to be one of the most important clinical ailments of the human society. The existing line of treatments has more side effects and caters less to the requirement of the poor people. Need of the hour is to explore an alternate therapeutic intervention that is safe & cost effective. Drugs rather than synthetic substance but of natural source are found to be more secure. In the present study, attempts were made to evaluate the Nephroprotective potential of aqueous extract of plant Trigonella foenum-graecum Linn. against gentamicin induced experimental renal damage. Wistar strains of albino rats were selected for the study and were divided into 6 groups. Group I served as normal control, Group II, III, IV & VI were induced with Gentamicin (80mg/kg bw intraperitoneally). Group II kept as Disease control, Group III & IV served as plant drug treated groups at the dose level of 150mg/kgbw, 300mg/kgbw and Group VI act as a standard drug control and Group V served as plant drug control. Various physical, biochemical and antioxidant parameters were studied using serum and kidney homogenate of experimental animals. Histopathological sectioning of kidney was also studied. From the data of the results obtained it was clearly evident that the group II animals showed symptoms of nephrotoxicity. The aqueous extract at the dose of 300 mg/kgbw showed potent nephroprotective activity which is comparable to that of standard drug treated group V.Hence, the results obtained in the present study, indicates that Trigonella foenum-graecum Linn. aqueous extract has the capability to treat nephrotoxicity induced by Gentamicin.